(untitled) (Heritage, 2020)
The aim of this paper is to examine theoretical demands and probable practical solutions within the development of online placement tests for both teaching and learning Serbian as a second language. Placement tests are used in the practice of teaching a foreign language in order to determine the level of language with the aim of forming homogenous groups, and these tests, in addition, do not necessarily have to be standardised. The development of modern information-communication technologies has set new challenges for the insufficiently developed practice of teaching Serbian as a second language. Among all those challenges, the one that stands out is the development of online tests for determining the level of one’s knowledge of the Serbian language. Accordingly, the authors have created an interactive test called Test Your Serbian, and it has shown, during its initial testing phase, the highest degree of accuracy (100%) in determining the level of the Serbian language (as a second language).